(untitled) (Analele Universității București. Informatică, 2024)
The paper aims to synthesize the thermo-mineral aquifer simulation methodology elaborated, in the 80s, at the Computing Center of the University of Bucharest, C.C.U.B. Professor Ion Văduva initiate a research contract between C.C.U.B. and the Geological Reserve Coordination Department of the Ministry of Geology, G.R.C.D. The result of this joint contract, carried out over several years, is the methodology presented in this paper. Based on this methodology, a software was written and successfully applied to optimize the exploitation of aquifers in the Oradea area.